Superficial Surgical Site Infection after Primary Closure Versus Delayed Primary Closure of Wound in Perforated Appendicitis - Yabinda Sahrish; Zainab Abdullah Kaludi; Shamaila Ayub; Khurram Zia; Muhammad Athar Khan; Nadia Khalid (Journal of Bahria University Medical and Dental College)
Objective: To assess the superficial surgical site infection after primary closure versus delayed primary closure of wound in perforated appendicitis. Study Design and Setting: This was an observational study conducted at Darul Sehat Hospital & Civil Hospital Karachi during March 2019 to August 2019 Methodology: All patients of either gender between 18-50 years of age undergoing open Appendectomy through standard gridiron incision in emergency having consented for participation in the study prior to surgery and with per-operative finding of perforated appendix in emergency were included. Patients on steroids or immunosuppressive agents, smoker staking 5 or more cigarettes per day, patients with history of Diabetes Mellitus, chronic liver disease and chronic renal failure were excluded from the study. Patients with perforated appendix were randomly allocated into two Groups. Group A received delayed primary closure at 3rd post-operative day while in Group B primary closure was done immediately after appendectomy. All patients were examined for signs and symptoms of superficial surgical site infection at the 5th postoperative day before discharge from the hospital. SPSS version 13 was used for data analysis. Chi square test was applied to compare the outcome (superficial surgical site infection) in both groups. P-value <0.05 was considered as significant. Results: A total sixty patients were allocated in each group. Wound infection was very high among patients with immediate closure (40%) as compared to group which received delayed primary closure (15%) (p=0.020). Conclusion: The superficial surgical site infection was significantly higher after primary closure versus delayed primary closure of wound in perforated appendicitis.